2018
DOI: 10.1002/admi.201801093
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Sandwiching of Reduced Graphene Oxide in Hierarchical Defect‐Rich MoS2 Ultrathin Nanosheets with Expanded Interlayer Spacing for Electrocatalytic Hydrogen Evolution Reaction

Abstract: The successful designing of low‐cost and highly active electrocatalytic materials from earth‐abundant elements are favorable for the large scale production of hydrogen from water splitting. Herein, the controllable sandwiching of reduced graphene oxide (RGO) in hierarchical defect‐rich MoS2 ultrathin nanosheets (MoSGMoS) with vertical alignment and expanded interlayer spacing is synthesized by hydrothermal method. The MoSGMoS product exhibits outstanding electrocatalytic activity for hydrogen evolution reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…As shown in Figure f and also in Figure S3 (Supporting Information), the layer number of MoS 2 nanosheets is in the range of 2–14 layers; the interlayer spacing of the MoS 2 nanosheets is about 0.75–0.95 nm, which is much larger than that of bulk MoS 2 (0.62 nm) . Furthermore, the defects in MoS 2 nanosheets can be observed in the HRTEM images (Figure S3, Supporting Information), which can also contribute to the enhancement of HER performance . The dark‐field TEM image of Ni@NC@MoS 2 (Figure g) and the corresponding elemental mapping images of Mo, S, Ni, C, and N (Figure h–l) further confirm the composition and the core–shell structure of the product.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As shown in Figure f and also in Figure S3 (Supporting Information), the layer number of MoS 2 nanosheets is in the range of 2–14 layers; the interlayer spacing of the MoS 2 nanosheets is about 0.75–0.95 nm, which is much larger than that of bulk MoS 2 (0.62 nm) . Furthermore, the defects in MoS 2 nanosheets can be observed in the HRTEM images (Figure S3, Supporting Information), which can also contribute to the enhancement of HER performance . The dark‐field TEM image of Ni@NC@MoS 2 (Figure g) and the corresponding elemental mapping images of Mo, S, Ni, C, and N (Figure h–l) further confirm the composition and the core–shell structure of the product.…”
Section: Resultsmentioning
confidence: 88%
“…The weakened pyridinic N peak in XPS spectrum of Ni@NC@MoS 2 compared to pure Ni@NC suggests the presence of some interaction between the N atoms and MoS 2 (Figure S4f,g). Due to the intrinsic layered crystal structure of MoS 2 , MoS 2 nanosheets grew mostly vertically on Ni@NC substrate to form Ni@NC@MoS 2 hierarchical sub‐microspheres …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal and solvothermal methods are the most interesting for the preparation of MoS 2 nanosheets [ 67 , 68 ]. In these methods, the Mo source is commonly a molybdate, such as Na 2 MoO 4 or (NH 4 ) 6 Mo 7 O 24 , and the S source is thiourea and thioacetamide and L-cysteine [ 69 , 70 , 71 , 72 , 73 ]. The molybdate reacts with the S or S compound in a stainless steel autoclave.…”
Section: Synthesis Of Mosmentioning
confidence: 99%
“…However, efforts are being made to further improve the catalytic activity of rGO. In particular, it has been reported that rGO doped with TM ions shows improved catalytic activity because the dopant ions increase the number of defect structures present on rGO [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%